Riqueza florística de Angiospermas del estado Lara depositadas en el Herbario “José Antonio Casadiego” (UCOB), Venezuela (2016)
A total of 6634 vascular plant specimens deposited in the UCOB Herbarium from Lara state until 2014 were reviewed in order to improve our knowledge about the flora. The most prominent collectors are Robert Smith, Hipólito Alvarado, Bolivia Mediomundo, Charles Burandt Jr., José Antonio Casadiego and Alcides Mondragón. 1659 species were recorded in 859 genera and 155 botanical families, accounting for 64.7% of the families, 36.5% of the genera and 11.3% of the Angiosperm species occurring in the country. Families with higher numbers of species were: Leguminosae (181), Poaceae (166), Asteraceae (125), Rubiaceae (95), Euphorbiaceae (65)and Malvaceae (54). Genera with higher numbers of species were: Paspalum (22), Miconia (20), Cyperus (19), Solanum (18), Piper (16), Senna (15) and Tillandsia (14). Of the total species, 308 are new records and four are endemic to Lara state. The most explored regions are: Serranía de Portuguesa, Serranía de Barbacoas, Serranía de Bobare and gallery forest of the Tocuyo River Basin. The most explored county was Morán (26.7 %), followed by Palavecino (18.8 %) and Iribarren (15,6 %), the least explored were Jiménez (3.7 %) and Torres (4.9 %) municipalities.